ANALISIS DIMENSI KINERJA ORGANISASI BADAN PENDIDIKAN DAN PELATIHAN PROVINSI JAWA TENGAH - Puspita, Selli; Yuniningsih, Tri; Mustam, Muhammad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
In the era of good governance the government has to have competent performance in serving the public . However, there are still many government organizations that have low performance . Whereas previously civil servants have been educated and trained . This can be seen from the performance of the Board of Education and Training of Central Java is still not optimal in producing competent personnel . This study aims to analyze the phenomenon of performance consists of four dimensions of performance , productivity , responsiveness , and accountability Responbilitas . Identifying the factors that support and hinder performance and formulate solutions that have been and will be done in improving the performance . This study used a qualitative descriptive approach and techniques as well as using a purposive sample taxonomic analysis .Â Based on the results of the discussion of research in Education and Training Agency of Central Java is known conclusion that the performance of the Board of Education and Training of Central Java is goodÂ in terms of quantity but the quality is not optimal . Judging from productivity , it can be quite good for achieving the target quantity is almost fulfilled . Judging from the responsiveness , still it is less because not capture the public 's aspirations . Judging from responbilitas , already based on the PP 101 of 2000 . Dililhat of accountability , it is good enough but no pertenggungjawaban to the public . Many factors affect the performance of the Board of Education and Training of Central Java Province which consists of factors supporting and inhibiting factors . To overcome the problems that occur in the process of performing the Board of Education and Training of Central Java province has made the solution be included in the employee Training Training Of Course and curriculum development .Â In order to improve performance by increasing productivity , through repairing the existing curriculum and the addition of competent lecturers in the Substantive Technical Training . For responsiveness and accountability through the use of the web . Responbilitas through increased reward and punishment.